The effectiveness of network marketing in enhancing market share: a case of Doves Assurance company - Marowa, Jane Talent (Midlands State University, 2017)
The study aimed at assessing the effectiveness of network marketing in enhancing market share of an organisation in the funeral sector in Zimbabwe. Doves Morgan was losing market share at a very alarming rate despite employing competitive strategies. The company therefore introduced Shiri plan network marketing strategy. The study therefore analysed the effects of referrals on market share, the commissions paid to network marketing agencies had an effect on market share through network marketing was likely to improve the market share of an organisation and lastly analysed the effects client prospecting on market share. The research used descriptive and explanatory research designs in finding the data. The study was conducted using a sample size of 40 respondents. Respondents were interviewed and completed questionnaires. The research findings were that commission given for recruiting new customers was attractive to non-members. More, so referrals have increased the market share of Doves because when agencies go out to source the customers those customers also refer others as well. Lastly client prospecting does not increase market share because most prospects promise that they will come and join the plan but they do not honour their promises. The study recommend that Doves Morgan should increase the amount of commission that is given to sales agencies for recruiting new members this is because money motivates people to get new assures for the Shiri plan. Most importantly under the referral system Doves Morgan should also use online referral system such as web browser on the websites.